PENGARUH TINGKAT PENDAPATAN UPAH MINIMUM REGIONAL (UMR), LITERASI EKONOMI, DAN PERILAKU KONSUMSI TERHADAP PENGELOLAAN KEUANGAN MAHASISWA - Mohammad Hatta Fahamsyah; Agung Tri Permana (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
This study aims to determine: (1) The effect of regional minimum wage income levels on financial management students. (2) Economic Literacy on Financial Management ofStudents. (3) Consumption Behavior on Financial Management of Students. This type of research is experimental research, namely research that strictly follows a scientific research design where this research method refers to a hypothesis testing or leads to a deductive research method, with the sample being FEB University Pelita Bangsa students with a total of 95 respondents using a purposive sampling technique. sampling. The results of this study are (1) The influence of Regional Minimum Wage Earnings has a significant positive effect on Financial Management (2) Economic Literacy has no significant positive effect on Financial Management (3) Consumption behavior has a significant positive effect on Financial Management.